Overview of BTX (Benzene, Toluene, Xylene) Production from Polyethylene Pyrolysis over Ga and Zn Modified HZSM-5 Catalyst - Yanewati, Shafira Hakim; Supramono, Dijan (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
The increase in Indonesia's BTX chemical production was carried out to keep pace with global demand trends. The raw material for alternative production is household waste in Indonesia, of which 36% is plastic. Polyolefins make up 76% of the composition of household plastic waste. The rapidly developed BTX production process is the depolymerization of polyolefin plastics by pyrolysis and catalyst modification for catalysis. Polyolefin plastic in the form of polyethylene produces the highest aromatic yield and selectivity among other types of plastic in plastic waste. This study compared two scenarios with the highest yield of aromatics using different catalysts as base literature with an additional overview regarding the topic related. The process scenarios being compared are polyethylene pyrolysis over CaO with Ga/ZSM-5 catalyst and Zn-ZSM-5 catalyst. Literature overview obtained the overall BTX production progress over time and the potential of polyethylene catalytic pyrolysis for further study